ACTH Prevents Deficits in Fear Extinction Associated with Early Life Seizures - Massey, Andrew T.; Lerner, David K.; Holmes, Gregory L.; Scott, Rod C.; Hernan, Amanda E. (Frontiers in Neurology, 2016)
Early life seizures are often associated with cognitive and psychiatric comorbidities that are detrimental to quality of life. In a rat model of early life seizures (ELS), we explored long-term cognitive outcomes in adult rats. Using ACTH, an endogeneous HPA-axis hormone given to children with severe epilepsy, we sought to prevent cognitive deficits. Through comparisons with dexamethasone, we sought to dissociate the corticosteroid effects of ACTH from other potential mechanisms of action. We found that while rats with a history of ELS were able to acquire a conditioned fear learning paradigm as well as controls, these rats had significant deficits in their ability to extinguish fearful memories. ACTH treatment did not alter any seizure parameters but nevertheless was able to significantly improve this fear extinction, while dexamethasone treatment during the same period did not. This ACTH effect was specific for fear extinction deficits and not for spatial learning deficits in a water maze. Additionally, ACTH did not alter seizure latency or duration suggesting that cognitive and seizure outcomes may be dissociable. Expression levels of melanocortin receptors, which bind ACTH, were found to be significantly lower in animals that had experienced ELS than in control animals, potentially implicating central melanocortin receptor dysregulation in the effects of ELS and suggesting a mechanism of action for ACTH. Taken together, these data suggest that early treatment with ACTH can have significant long-term consequences for cognition in animals with a history of ELS independently of seizure cessation, and may act in part through a CNS melanocortin receptor pathway.